Study of microClimate Characteristic in Tamansari Yogyakarta as a Heritage Tourism Area - Octarino, Christian Nindyaputra; Noviandri, Patricia Pahlevi (Jurnal Arsitektur dan Perencanaan (JUARA), 2021)
Yogyakarta is known as a Tourism City because there is a lot of tourist destination that exists. One of the uniqueness of the city of Yogyakarta is the royal system that has been part of the government until this day. Tamansari Water Castle is a historic site used by the King and also the royal family for recreation. As one of the main destinations for tourists, it is important to note how the performance of the space formed in providing comfort for visitors. This study aims to determine how the microclimate characteristics in the Tamansari area, which have an impact on the thermal comfort felt by visitors. Observations are made to discover the elements forming the outdoor space such as the building mass layout and composition, the type of surface material, and also the type of vegetation that exists. This study uses simulation method with Envi-met software, using observational data as input. The simulation process will show how the microclimate conditions are formed in the Tamansari area, which includes air temperature, humidity, wind speed, and wind movement. The results represent that the landscape design in Tamansari has considered the thermal comfort through surface material and vegetation they have.